Studies on diffuser augmented micro wind turbine - AMPILI A. G; Syamkrishnan R; Vishnupriya S; Dr. Sathyajith Mathew (Guide) (Tavanur 2005 Kelappaji College of Agricultural Engineering and Technology)
Studies on diffuser augmented micro wind turbine
Studies on diffuser augmented micro wind turbine